A description of the components of a specialist younger-onset dementia service: a potential model for a dementia-specific service for younger people. (February 2022) - Loi, Samantha M; Walterfang, Mark; Kelso, Wendy; Bevilacqua, JoAnne; Mocellin, Ramon; Velakoulis, Dennis
Objectives: This narrative paper describes the influences behind the development of, and key components of a specialist younger-onset dementia service located in metropolitan Victoria, Australia. Conclusion: The Melbourne Young-Onset Dementia Service was established in 2013 and provides diagnosis and ongoing care for people with younger-onset dementia and their families, through collaboration with other medical units, allied health and community services. It is potentially a model for other younger-onset dementia services nationally and internationally.